Schistosomiasis Control Strategies in The Tropics: A Review - Ramadhan Tosepu; Magvirah Tuljannah (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Schistosomiasis remains a major neglected tropical disease and continues to constitute a significant public health challenge in several endemic areas, particularly in Central Sulawesi, Indonesia. The disease is transmitted through freshwater snails that serve as intermediate hosts, resulting in chronic health consequences that adversely affect population health status, labor productivity, and broader socioeconomic development. Objective: This study aims to identify and critically analyze schistosomiasis control strategies that have been implemented in tropical settings, with particular emphasis on the effectiveness of interdisciplinary and participatory approaches in reducing disease transmission. Methods: This study employed a literature review design by analyzing ten peer-reviewed research articles reporting schistosomiasis control interventions. The reviewed strategies encompassed technical, behavioral, regulatory, and cross-sectoral approaches. Data were analyzed descriptively to assess the effectiveness, implementation processes, and outcomes of the various control strategies. Results: The findings demonstrate that integrated control strategies were effective in significantly reducing schistosomiasis prevalence. These strategies included environmental modification to reduce or eliminate freshwater snail habitats, application of molluscicides, improvement of community knowledge, attitudes, and practices through health education, enforcement of village-level regulations, and strengthening of disease surveillance systems and intersectoral collaboration. Conclusion: Effective schistosomiasis control in tropical regions requires the concurrent implementation of technical and social interventions. Community-based and participatory approaches, supported by strong local policy frameworks and sustained cross-sectoral collaboration, are critical determinants for achieving long-term control and eventual elimination of schistosomiasis.